A legal analysis of security for women using public transport in Malaysia / Fatin Illinie Mohamad Rudzi…[et al.]. - Mohamad Rudzi, Fatin Illinie; Farahin Zainal, Nur Adnin; Megat Sharizal Amri, Puteri Shazren Nabilla; Shahruddin, Syarafina (2014)
In recent years, women have been targeted more by crime offenders and unfortunately Malaysia was ranked at 7th place for being the most dangerous transport system for women. The purpose of this paper is to solve the current problem which is the number of sexual crime towards women should be reduced. This paper also helps in fulfilling the demand of women from the pressure group and the NGOs. The paper will also give advantages to the law maker or the policy maker in our country in giving suggestions to revamp our public transport system. Our local authorities should take extra initiatives to ensure the security of women when traveling daily in public transport and do not let a good infrastructure of public transport to go waste by having a society that harmful to women. Even ASEAN tend to overlook the need of women particularly in transportation. The gap in connectivity may need to be narrowed down to achieve better transportation system. Although this matter has been recognized by most of the countries in the world yet not so many initiative has been taken as only few countries has come up with any specific law or provision concerning this matter. Thus, short and long term strategies had been suggested in this paper in order to revamp our public transportation system for good.